2011
DOI: 10.4208/aamm.10-m1030
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of Elasticity and Viscoelasticity for Solids

Abstract: Abstract. There are a number of interesting applications where modeling elastic and/or viscoelastic materials is fundamental, including uses in civil engineering, the food industry, land mine detection and ultrasonic imaging. Here we provide an overview of the subject for both elastic and viscoelastic materials in order to understand the behavior of these materials. We begin with a brief introduction of some basic terminology and relationships in continuum mechanics, and a review of equations of motion in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(155 citation statements)
references
References 42 publications
1
146
0
1
Order By: Relevance
“…(1) is computed from these elements, see e.g. [42]. It is important to note that those springs and dashpots do not have a direct physical interpretation.…”
Section: Viscoelasticitymentioning
confidence: 99%
“…(1) is computed from these elements, see e.g. [42]. It is important to note that those springs and dashpots do not have a direct physical interpretation.…”
Section: Viscoelasticitymentioning
confidence: 99%
“…, N , is given. Then, the system (21) defines a system of functions ψ (1) j (y), which are substituted into the system (22), and a new choice with regard to the variable x is defined as ϕ (2) j (x). Then, using the chosen functions, the system (21) yields a new function ψ (3) j (y) with respect toy, and so on.…”
Section: Methods Of Variational Iteration (Mvi)mentioning
confidence: 99%
“…Owing to MVI, a solution to Eq. (16) can be searched in the form of (17), where the functions ϕ i (x) and ψ i (y) are defined through the following equations (22) in the following way. A certain system of N functions with regard to one of the variables, let us say ϕ 0 j (x) j = 1, 2, .…”
Section: Methods Of Variational Iteration (Mvi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Various results, examples and mechanical interpretations in the study of viscoelastic materials of the form (1), can be found in [4] and the references therein. Such kind of constitutive laws were used in the literature in order to model the behavior of real materials like rubbers, rocks, metals, pastes and polymers.…”
Section: K(t − S)ε(u(s)) Dsmentioning
confidence: 99%